The global invasion risk of rice yellow stem borer Scirpophaga incertulas Walker (Lepidoptera:Crambidae) under current and future climate scenarios. - Shravani Sanyal; A V M Subba Rao; H Timmanna; G Baradevanal; Santanu Kumar Bal; M A Sarath Chandran; P R Shashank; V K Singh; P K Ghosh (PLoS ONE)
Rice yellow stem borer, Scirpophaga incertulas (Walker) (Lepidoptera: Crambidae) is a serious pest, that causes significant yield loss (10-40%) to rice crop in India and other parts of the world. This study emphasizes the prediction of the potential invasion risk, distribution, and further spread of S. incertulas during current and future climate change scenarios in India and the world. The pest identity was confirmed with morphological taxonomy, and the possible habitat distribution and further spread in future climate scenarios were modelled using the MaxEnt algorithm. The climate niche for S. incertulas was also established by analyzing the correlation between the pest occurrence data of 143 locations in India and seven bioclimatic variables viz., bio01, bio02, bio03, bio05, bio12, bio13, and bio15, were chosen for predicting the distribution of S. incertulas. The model performance was good as it exhibited a strong Receiver Operating Characteristic Curve value of 0.949. Based on the Jackknife test, the Bio 13 (precipitation of the wettest month), exhibited the highest gain value and emerged as the primary abiotic factor exerting influence on the potential habitat distribution of this borer. The study demonstrated that bioclimatic variables annual mean temperature (30 °C), and annual precipitation (10-700 mm) favour its multiplication, infestation, and further spread to new areas. As the anticipated habitat range of S. incertulas is of considerable importance for researchers and other stakeholders involved in plant protection, the data generated here may be useful for researchers, policymakers, and farmers for designing better management strategies to mitigate this pest and curtail its spread to new rice growing areas in a rapidly changing global environment.